Strategies for constructing manganese-based oxide electrode materials for aqueous rechargeable zinc-ion batteries - Liu, Ying; Wu, Xiang (Chinese chemical letters, 2022)
Commercial lithium-ion batteries (LIBs) have been widely used in various energy storage systems. However, many unfavorable factors of LIBs have prompted researchers to turn their attention to the development of emerging secondary batteries. Aqueous zinc ion batteries (AZIBs) present some prominent advantages with environmental friendliness, low cost and convenient operation feature. MnO2 electrode is the first to be discovered as promising cathode material. So far, manganese-based oxides have made significant progresses in improving the inherent capacity and energy density. Herein, we summarize comprehensively recent advances of Mn-based compounds as electrode materials for ZIBs. Especially, this review focuses on the design strategies of electrode structures, optimization of the electrochemical performance and the clarification of energy storage mechanisms. Finally, their future research directions and perspective are also proposed. A plenty of work has focused on polymorphic Mn-based compounds due to their non-toxicity, low cost and rich crystal structure. In fact, the connection mode of MnO6 octahedrons determines MnO2 crystal structure, including α-, β-, γ-, λ-, R-, δ-, ε- and T-MnO2. These structures can be mutually transformed and seriously affect their electrochemical performance [Display omitted] .